Perceived career opportunities from globalization: globalization capabilities and attitudes towards women in Iran and the US - Newburry, William; Belkin, Liuba Y; Ansari, Paradis (Journal of International Business Studies, 2008)
As competition for human capital intensifies, understanding how employees perceive their fit in a company can assist companies in harnessing the knowledge and skills needed to achieve competitive advantage. Building on the person–organization fit theoretical framework, we suggest that individual employee perceptions of globalization-related career opportunities represent a fit between individual and company capabilities and values. We find both similarities and differences between the relationships of individual- and company-level globalization capabilities and attitudes towards women (an important capability source) and globalization-related career perceptions within samples of 96 Iranian and 210 US employees.